Development of Numeracy Problems with the Context of Herbal Medicines in Junior High School - Rahmah Johar; Aini Wahyuna; Erni Maidiyah; Ratu Fazlia Rahmayani; Fahlida Harnita (Universitas Syiah Kuala, 2022)
Individuals with low immune systems have a higher impact on the Covid-19 outbreak. Herbal treatment is one of the solutions to reduce the risk of being infected by the virus. However, the public has not yet fully known about herbal medicines in Indonesia. One of the efforts to increase students' knowledge about herbal medicine is by developing numeracy questions in the context of herbal medicine. This study aims to produce valid and reliable numeracy questions in the context of herbal medicine for junior high school students and to find student responses to numeracy questions in the context of herbal medicine. The research method used is a design research type of development study with a Tessmer development model. The results of the study were 16 numeric questions with the context of herbal medicines that were valid in terms of content, construct, and language based on the validator's assessment, while nine of the 16 questions met empirical validity. The numeration question set in the context of herbal medicine has a high-reliability value. Based on the students' responses, the set of questions developed positively impacted students. The teacher can use these questions as an instrument to train students' numeracy ability.